MEMPERKUAT IDENTITAS GENERASI BUDDHIS YANG UNGGUL BERLANDASKAN NILAI-NILAI BUDDHAYANA (BUDDHIS CAMP PEMUDA BUDDHAYANA SEPROVINSI NTB) - RAPIADI, RAPIADI; SENERU, WISTINA; SAPUTRI, VIKE APRILIANIN MARWINTARIA; PANNA, PANNA; KRISTIANTO, ADI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
The Buddhist Camp activities for Buddhayana youth throughout NTB Province which will be held on 07–09 April 2023 at Vihara Jaya Wijya, North Lombok, West Nusa Tenggara, carry the theme